A study on the antiantigenicity of the glycoproteins on the mumps virus and how it is related to the acute and infections of the encephalitis in newborn hamsters / Tengku Elida Tengku Zainal Mulok - Tengku Zainal Mulok, Tengku Elida (Universiti Teknologi MARA, Pahang, 1998)
The surface location of viral glycoproteins, their involvement in interactions with the cell and their role, reveal that these proteins are the antigens to which immunity develops if viral diseases are presented by immunological means. The F and the HN glycoproteins have their own specific activities. The discussion will concentrate mainly on the Kilham strains. The properties of the viral NANase influence the process of virus - induced cell fusion, and thus may contribute to cytopathology in tissue culture which correlates with the pathogenicity in vivo.